Preliminary Stability Estimation And Analysis Of AEROMECH I UAV Using DATCOM Software - Abdullah, Azizul (2012)
Stability is one aspect of the aircraft performance. Conventional methods such as wind tunnel test, flight test and Computational Fluid Dynamics (CFD) are used for the estimation and analysis of the stability during aircraft design process. Those methods are time consuming and expensive because they cannot determine the stability coefficients directly. Thus, as one of the promising alternative methods, the DATCOM software was employed in the present study, in order to estimate the aerodynamic coefficients and analyze the static and dynamic stabilities at the preliminary design stage of a small Unmanned Aerial Vehicle,